2016
DOI: 10.7717/peerj.2642
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical models are a powerful method to understand and control the spread of Huanglongbing

Abstract: Huanglongbing (HLB), or citrus greening, is a global citrus disease occurring in almost all citrus growing regions. It causes substantial economic burdens to individual growers, citrus industries and governments. Successful management strategies to reduce disease burden are desperately needed but with so many possible interventions and combinations thereof it is difficult to know which are worthwhile or cost-effective. We review how mathematical models have yielded useful insights into controlling disease spre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 50 publications
1
32
0
1
Order By: Relevance
“…The trait‐based thermal biology approach illustrated here for mosquito‐borne diseases can be applied more broadly to understand the effects of climate change on many other types of vector‐borne diseases, including plant diseases transmitted by aphids, flies, and psyllids (Taylor et al , ) and human and livestock diseases transmitted by biting midges, fleas, and flies (Akey et al ; Carpenter et al ; Moore et al ; Alsan ), and tick‐borne diseases (Ostfeld & Brunner ; Cheng et al ). However, differences in vector and host biology, including the effects of vector life history and biting behaviour and how they interact with host activities and life cycles, can cause major differences between the models presented here (eqns ) and the transmission models most appropriate for other systems.…”
Section: Discussionmentioning
confidence: 99%
“…The trait‐based thermal biology approach illustrated here for mosquito‐borne diseases can be applied more broadly to understand the effects of climate change on many other types of vector‐borne diseases, including plant diseases transmitted by aphids, flies, and psyllids (Taylor et al , ) and human and livestock diseases transmitted by biting midges, fleas, and flies (Akey et al ; Carpenter et al ; Moore et al ; Alsan ), and tick‐borne diseases (Ostfeld & Brunner ; Cheng et al ). However, differences in vector and host biology, including the effects of vector life history and biting behaviour and how they interact with host activities and life cycles, can cause major differences between the models presented here (eqns ) and the transmission models most appropriate for other systems.…”
Section: Discussionmentioning
confidence: 99%
“…Both the standard identification of differentially expressed genes as well as decision tree construction revealed the gene VvDMR6 from the 2OG-Fe(II) oxygenase gene superfamily, which showed the highest similarity (69%) to the sequence of the gene DMR6 from Arabidopsis (At5g24530) (Van Damme et al 2008). Although its biological role is not known at the moment, it has been shown that Arabidopsis plants lacking a functional DMR6 gene have reduced susceptibility to downy mildew (Van Damme et al 2008). In addition, it has been suggested that it acts as a suppressor of plant immunity (Zeilmaker et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Combining all these imperfect and very diverse data in a suitable model to describe and explain the pathogenicity is a methodological challenge, because several factors may introduce uncertainties at different stages of the model construction (Taylor et al 2016). Recently, a Bayesian inference with generalized linear mixed effect models has suggested that vector presence is not the only and not the most important factor for BN prevalence, but environment and grapevine cultivar also contribute to the disease development (Panassiti et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This search should also include research focused on disease-free citrus production areas, to diagnose the potential risk, such as studies that include the geotechnologies: spatial modelling, simulation of risk areas and map algebra (Magarey et al, 2007;Ladányi, 2010;Gutierrez et al, 2011;Rosa et al, 2011;LANGIF, 2015;NAPPFAST, 2015;Narouei et al, 2016;Taylor et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of HLB in Africa, Asia and America led to studies on its economic and social impact in affected countries; in all cases, the results point to huge losses associated with the disposal of infected trees and the rise in production costs due to management practices to prevent the disease (Taylor et al, 2016). Diaz et al (2014) focused on the environmental conditions that foster the presence, abundance and population growth rate of D. citri.…”
Section: Introductionmentioning
confidence: 99%